Psychosocial Interventions for Depressive and Anxiety Symptoms in Individuals with Chronic Kidney Disease: Systematic Review and Meta-Analysis - Pascoe, Michaela C.; Thompson, David R.; Castle, David J.; McEvedy, Samantha M.; Ski, Chantal F. (Frontiers in Psychology, 2017)
Purpose: Depressive and anxiety symptoms are common amongst individuals with chronic kidney disease and are known to affect quality of life adversely. Psychosocial interventions have been shown to decrease depressive and anxiety symptoms in various chronic diseases, but few studies have examined their efficacy in people with chronic kidney disease and no meta-analysis has been published. Thus, the aim of the present systematic review and meta-analysis was to evaluate the effects of psychosocial interventions on depressive and anxiety symptoms as well as quality of life in individuals diagnosed with chronic kidney disease and/or their carers. Methods: In this systematic review and meta-analysis, we included published randomized controlled trials comparing psychosocial interventions versus usual care for impacting depressive and anxiety symptoms and quality of life. Results: Eight studies were included in the systematic review and six of these were subjected to meta-analysis. Psychosocial interventions were associated with a medium effect size for reduction in depressive symptoms and a small effect size for improved quality of life in the in individuals with chronic-kidney-disease and their carers. Some evidence suggested a reduction in anxiety. Conclusion: Psychosocial interventions appear to reduce depressive symptoms and improve quality of life in patients with chronic-kidney-disease and their carers and to have some beneficial impact on anxiety. However, the small number of identified studies indicates a need for further research in this field.